Peran Pasar Sawang terhadap Pengembangan Ekonomi Masyarakat Desa Gempol - Maulana , Hendra; Ciptaningtyas, Intan Savitri; Pertiwi , Mega Agustina Kesumaning; Djaja , Michael Samudra; Fauziyyah, Rima (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
The market is a place where sellers and buyers meet to carry out transactions, a means of social and cultural interaction, and community economic development. Sawang Market is a market with a traditional concept pioneered by students of KKN-T MBKM Group 02 in Gempol Village. This market emerged because according to the results of observations of the village's economic activities which were considered to be underdeveloped. The research methods used are observation, interviews, and literature studies. the benefits felt through the sawang market are that it can improve the economy of the gempol village community, increase community confidence in entrepreneurship. other benefits felt are that it makes it easier for housewives to get raw material products to food products easily and the community can socialize. village officials fully support this activity because it can develop the gempol village community to explore the entrepreneurial spirit. Therefore, all parties expect the sustainability of the Sawang Market activities. Keyword : Economy,Pasar Sawang, Development